Dampak Etos Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan PT. Nusa Cendana Inti Perkasa Muara Enim - Samsi, Romsa Endrekson; Marina, Resi (Sekolah Tinggi Ekonomi Islam Al-Furqon Prabumulih, 2024)
The work environment has an important role in improving employee performance through a good physical and non-physical environment, such as creating a safe and comfortable atmosphere for employees, including providing work safety facilities and tools, maintaining the cleanliness of the workplace, and increasing employee morale in every activity. , so that physical and non-physical conditions are adequate, work productivity will increase. Work ethic is work enthusiasm or taste for work that shows the enthusiasm for collaboration, debate and achievement, so that you can actually reap real results and contribute to the progress of the organization. Employee performance is the ability to achieve job requirements, namely when work targets can be completed at the right time or without exceeding the time limit provided so that the goals will be in accordance with the company's morals and ethics. This research aims to determine the impact of the work environment and work ethic on employee performance at PT. Nusa Cendana Inti Perkasa Muara Enim. The population and sample in this study were 60 people from all employees of the production division of PT. Nusa Cendana Inti Perkasa Muara Enim. The research data was analyzed using multiple linear analysis which was processed with the help of the Statistical Package for the Social Sciences (SPSS) computer program version 26. The results of this research indicate that there is an impact of the work environment and work ethic on employee performance at PT. Nusa Cendana Inti Perkasa Muara Enim.. With a significant F of 0.000 < 0.05. Multiple linear regression equation Y = 35,908 + 0,184 X1 + 0,582 X2 PT. Nusa Cendana Inti Perkasa Muara Enim. 0.000 < 0.05. There is an impact of the work environment and work ethic on employee performance. PT. Nusa Cendana Inti Perkasa Muara Enim. with a significant value of 0.000 <0.05.